Combined conditioning of inorganic coagulant and polyamine to improve the dewaterability of municipal sludge, minimize dosage and reduce the influence of filtrate. (13th February 2023) - Hua, Baolv; Zhao, Shichao; Li, Fengting
Abstract: Efficient dewatering of sludge is necessary for its cost-effective transportation and final disposal. However, the common method of using polyferric sulfate (PFS) and polyacrylamide (PAM) requires a large amount of dosage and produces high iron ion content in the filtrate. This study examined a solution of applying polyamine (PA) coupled with inorganic coagulant PFS. The results demonstrated that using PFS + PA together could achieve the same or similar filtering rates as using PFS + PAM. The capillary suction time (CST) of PFS + PA (89.0 s) was equivalent to that of PFS (75.1 s) and better than that of PA (117.1 s) and raw sludge (RS, 403.8 s). Compared with PFS + PAM, the combination of PFS and PA efficiently removed Fe ions and chemical oxygen demand (COD) in sludge water content, with Fe ions in the sludge filtrate reduced by 97.8% and COD reduced by 78.9%, respectively. By analyzing the basic physicochemical properties of the sludge system, including the synergistic effect of coagulation and flocculation, sludge hydrolysis and flocculation, it indicated that PA + PFS could reduce bound water. These results demonstrated that combining PFS and PA to improve sludge dewatering performance is more beneficial than utilizing a coagulant or flocculant alone, even PFS + PAM. HIGHLIGHTS: Pretreatment of sludge with minimal chemicals. Reduction of metal content in the treated sludge filtrate. Graphical Abstract